DETERMINATION OF EVAPOTRANSPIRATION BASING ON SOLAR RADIATION IN HOA BINH PROVINCE - Hung Chien, Le; Thi Oanh, Nguyen; Thi Thom, Tran (Journal of Forestry Science and Technology, 2023)
In the management, planning of agro-forestry and water resources, the determination of evapotranspiration is extremely important, evapotranspiration (ET) is a parameter that needs to be determined in many practical applications. The content of the article presents 4 methods to determine the amount of evapotranspiration: Turn (1961), McGuinness and Bordne (1972), Makkink (1957), Doorenbos and Pruitt (1977). All methods use meteorological data directly measured at hydro-meteorological stations in Hoa Binh province to calculate the value of solar radiation energy to estimate the average daily evapotranspiration. The results of evapotranspiration calculation by the methods are compared and the accuracy is evaluated based on direct measurement data at hydro-meteorological stations in the province. Applying the formula to calculate ET according to the following methods: Turn (1961), McGuinness and Bordne (1972), Makkink (1957), Doorenbos and Pruitt (1977), obtained ET values ​​of 6.2 mm, 6.3 mm, 8.1 mm, 9.3 mm, respectively. Mean square error of evapotranspiration at meteorological stations calculated by the methods of Turn (1961), McGuinness and Bordne (1972), Makkink (1957), Doorenbos and Pruitt (1977), compared with the average evapotranspiration at meteorological stations measured directly is 2.1 mm, 1.9 mm, 1.3 mm, 1.9 mm respectively. The study shows that Makkink (1957) method with coefficients a = 0.9, b = 0 is suitable for calculating evapotranspiration at Hoa Binh area.